Life on earth a natural history - Attenborough, Richard, -1926; British Broadcasting Corporation (Burbank : Warner Home Video Inc., 1990)
Its about the story of how a few of those life forms came to be as they are, not as isolated oddities but as elements in a long and continuous story that began billions of years ago
This set is consists of two video cassettes. V.1; - p.1. The infinite variety - p.2. Building bodies - p.3. The first forests - p.4. The swarming hordes - p.5. Conquest of the waters - p.6. Invasion of the land - V.2; - p.7. Victors of the dry land - p.8. Lords of the air - p.9. The rise of the mammals - p.10. Theme and variations - p.11. The hunters and the hunted - p.12. Life in the trees - p.13. The compulsive communicators
Keywords: Evolution (Biology); Zoology -- Miscellanea